The Influence of Corporate Culture on Employee Adaptability During Organizational Change at PT Sido Muncul Tbk - Genoveba Moreira Rato Lopes; Darwati Susilastuti (Jurnal Multidisiplin Indonesia, 2025)
This study aims to examine the influence of corporate culture on employee adaptability during organizational change at PT Sido Muncul Tbk. The method used is a qualitative approach with in-depth interviews and literature review. Interviews were conducted with 10 respondents from various managerial and operational levels to explore their views on corporate culture and how that culture affects employees' ability to adapt to ongoing changes. Additionally, the study reviews relevant theories to support the analysis. The results show that an open, inclusive corporate culture that supports effective communication plays an important role in facilitating employee adaptation to change. Conversely, a more hierarchical and less flexible culture can hinder the adaptation process. This research provides insights for company management to design change strategies that consider cultural aspects to support a smooth organizational transition..